Blinding Induced Risk of Bias in Randomized Controlled Trials of Physiotherapy Interventions — A Retrospective Study - Joseph John; Naveen Kumar I (Journal of Clinical and Biomedical Sciences)
Introduction: In randomized clinical trials, the methodological idea of preventing bias by withholding knowledge of the allocation status is known as blinding. Blinding refers back to the concealment of group allocation from one or extra individuals concerned in scientific studies, most commonly a randomized controlled trial (RCT). Even though randomization minimizes variations among treatment groups on the outset of the trial, it does nothing to prevent differential treatment of the groups later within the trial or the differential assessment of outcomes, either of which may also bring about biased estimates of treatment outcomes. The most beneficial strategy to limit the chance of differential remedy or assessments of results is to blind as many individuals as viable in a trial. Objective: To study the extent of blinding induced bias in RCT of physiotherapy interventions and to evaluate the extent of interpretative consideration it the trials are not blinded in the sample of RCT included. Methodology : We conducted a retrospective analysis to estimate the blinding bias in the randomized controlled trials published in physiotherapy interventions from 2016 to 2022. Results & Conclusion : We included 50 RCTs for blinding assessment. About 88% of included articles were not having participants blinding 90% has not done therapist blinding and nearly 50% of studies were conducted without assessors blinding. Based on the results of this study blinding of important participants were infrequently reported in the included studies. Keywords: Blinding, Risk of bias, Physiotherapy, Randomized controlled trials